2011
DOI: 10.1016/j.pmrj.2011.08.448
|View full text |Cite
|
Sign up to set email alerts
|

Poster 418 Improving Patient Handoff for Acute Rehabilitation Admission

Abstract: is obtained after residency. We found no evidence that informal learning of practice management principles occurs during residency. Identified knowledge gaps span the spectrum of practice management principles and can guide future curriculum development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A recent presentation reported that 83% of discharge paperwork received by a CIIRP lacked important information. 14 The discharge summary, or discharge paperwork, is foundational for continuity of care for patients discharged from acute services. This summary is especially important for patients admitted to CIIRPs, where close monitoring by physicians and nurses is required to ensure patient safety and optimal outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent presentation reported that 83% of discharge paperwork received by a CIIRP lacked important information. 14 The discharge summary, or discharge paperwork, is foundational for continuity of care for patients discharged from acute services. This summary is especially important for patients admitted to CIIRPs, where close monitoring by physicians and nurses is required to ensure patient safety and optimal outcomes.…”
mentioning
confidence: 99%
“…A recent presentation reported that 83% of discharge paperwork received by a CIIRP lacked important information. 14…”
mentioning
confidence: 99%